INSEGNARE IL LESSICO CON I DIZIONARI DELL’USO (ItalianoLinguadue, 2025)
Teaching vocabulary with usage dictionaries In this article, adopting an interdisciplinary approach, we propose a series of lexical-focused instructional activities especially designed for students in the first years of the secondary cycle. Athough focused on lexis, some of them can also facilitate the development of general and transferable communication skills (commonly referred to as soft skills). We will focus on one among the topics that can be related to lexis teaching and learning: the knowledge and use of synchronic dictionaries. In order to facilitate the organization of instructional activities in many educational contexts, it has been decided to resort, where possible, to the use of easily accessible lexicographic tools: namely those freely available on the Web. The text is divided into two sections: the first one provides information on usage dictionaries as a fundamental cognitive requisite; the second one presents a teaching unit comprising five lessons, with an estimated total duration of fifteen hours. The unit is designed as modular, allowing the instructor to select and adapt its components as needed; at the same time, each component is interconnected, so as to ensure a coherent and comprehensive learning experience. Due to space limitations, only one of the proposed lessons will be developed in these pages as an example, leaving it to the teachers to elaborate on the parts that are still missing.